During virtual anatomy sessions, do educators and learners feel more at ease or anxious? Revisiting the Covid-19 lock down times - Amol Ashok Shinde; Dinesh K Patel; Purushottam Rao Manvikar (Wolters Kluwer Medknow Publications, 2023)
Background: The COVID-19 pandemic forced the entire education system to accept online teaching as the only way to complete the stalled MBBS teaching-learning. Later, the hybrid mode of teaching was started in many colleges. This study is a revisit to lockdown times from teacher's and learner's points of view to determine the various difficulties faced by teachers and learners during online classes. Methodology: In this longitudinal questionnaire-based survey, questionnaires in English were given to 750 MBBS students of 2019-2020, 2020-2021, and 2023-2024 batches and 47 MBBS teachers. Results: Sixty-three percent of students strongly agreed to selecting classroom lectures over online classes. Teachers faced technophobia in app-based education (39%) and absence of response while teaching (18%) as difficulties during online classes. Internet connection issues and unfriendly learning management system applications were the issues faced by the students. Conclusion: The integration of offline and blended learning can make teaching by teachers and interpretation by students better.